MINI REVIEW: PENGEMBANGAN BIOSENSOR KOLORIMETRI BERBASIS AGREGASI NANOPARTIKEL EMAS - Hana Verdiani; Dinda Syafira; Husna Nugrahapraja (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2023)
Gold nanoparticle (AuNP) is a material commonly used in colorimetric detection for biological sensors due to its low production cost, simplicity, and ease use. AuNP is known to generate different colors depending on the particle aggregation level. In the last two decades, changes in AuNP aggregation status have become the basis for developing a sensor to detect analytes in the sample. The solution color changes could be observed without sophisticated equipment, allowing ,more straightforward interpretation of the detection result. This review focuses on developing AuNP aggregation-based colorimetric tests for detecting various biological analytes. It discusses multiple mechanisms, strategies, functionalization, the latest research, and perspectives of AuNP use in colorimetric detection, which could be considered for future biosensor development. The concept of colloidal gold nanoparticle aggregation and stabilization is emphasized in this review.Â